Parents as confirmation sponsors: Canon 893 - Daly, Brendan (Roman Replies and CLSA Advisory Opinions 2009, 2009)
"The office of sponsor has a long tradition in the Catholic Church, dating probably from the middle of the second century. The practice of parents acting as sponsors for their children was common in the fourth century, as a letter of Saint Augustine to Bishop Boniface indicates. However, by the ninth century, Church Councils, such as those of Munich and Aries in 813, forbade parents to be sponsors at the baptism of their children. Canons 765 and 795 of the 1917 Code of Canon Law also forbade parents to be sponsors at the baptism or confirmation of their children. How is this matter treated in the 1983 Code of Canon Law?"